PENGARUH LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA KOTA SAMARINDA - Guswari, Muhammad Fachri; Sofia Ulfa Eka Hadiyanti; Vera Anitra (Asosiasi Ahli Administrasi Indonesia, 2025)
This study aims to analyze the effect of the physical work environment on employee performance at the Samarinda City Manpower Office. The method used is a quantitative approach with a correlative type of research. Data collection was carried out through distributing questionnaires to 60 respondents who were active employees at the Samarinda City Manpower Office. The analysis techniques used include validity, reliability, classical assumptions, and simple linear regression tests using SPSS version 25. The results showed that the physical work environment has a significant effect on employee performance. This proves that improving the quality of the physical work environment is in line with improving employee performance. The practical implication of these findings is that the management of the Manpower Office of Samarinda City needs to pay more attention to physical factors in the workplace such as lighting, ventilation, temperature, and ergonomic layout as part of a strategy to increase productivity. Implementation of improvements in the physical work environment based on empirical results can be a concrete step in supporting bureaucratic reform and improving the quality of public services. The novelty of this research is its focus on local government agencies which are still rarely the object of research in the context of the relationship between the physical work environment and performance. This research provides an up-to-date empirical contribution using a systematic quantitative approach, as well as providing local evidence relevant to the development of public sector human resource management in Indonesia.